La tanatopolítica y su violencia. Efectos subjetivos - Imbriano, Amelia Aydée (Editorial Bonaventuriana, Universidad de San Buenaventura Cali., 2011)
Here in this book are formulated the central questions of our homecoming: How to found an active solidarity, and how to conjure Circe's charm that held Ulysses for so long, not without his consent? In short, how to get out of the labyrinth that imprisons Theseus, how to melt the thanatic aporia. Today a new jus-gentium based on the inalienable rights of the dignity of the person is being vigorously born under all the banners of the world. This global right of protection of the fundamental rights protected, the conventions and norms of the United Nations and of all the national and international courts, together with a new International Humanitarian Law, point the way back home, and from there all the prisoners of Circe are freed, from there they return home, which are none other than the bloody despotisms for which the last century and the beginning of this one will be known and repudiated, together with the genocide of entire populations, as attested by the cases of our International Criminal Tribunal for the former Yugoslavia and Rwanda and other international and regional human rights forums. This new language exists. This task is also incumbent upon legal language, since the norm in its logical context of normative imputation refers to intersubjective conduct, as Giorgio Del Vecchio, the great Italian philosopher, had expressed decades ago. The inscription of the norm, the discrimination between what is permitted and what is forbidden, and its consequent legal metaphor, -in the author's expression following Legendre-, constructs human subjectivity, which can only be thought of as intersubjectivity Amelia has already started vigorously in that direction!